How to protect the clean athletes - Müller, D. (German Journal of Exercise and Sport Research, 2017)
Anti-doping work can only be successful if athletes are not only participating, but actively engaging and promoting their right to compete in clean and fair sport. To achieve this, there is a strong need for strategic realignment, improvement of doping control programs, support from criminal investigating bodies, as well as structural and person-centred prevention. Anti-doping work needs full independence from the sport establishment to be credible and effective. A real separation of powers implies the establishment of an "International Anti- Doping Service" (IADS) as a missing link in the international anti-doping framework besides the World Anti-Doping Agency (WADA) and the Court of Arbitration for Sport (CAS). WADA must be strengthened to impose sanctions on noncomplying organisations and countries, based on accreditation and review processes, benchmarking and quality controls. The highest standards of good governance must apply to anti-doping organisations. Sports organisations, major event organizers, sport sponsors, media institutes and public authoritiesmust contribute to a global antidoping fund to provide sufficient funding for the new anti-doping framework. The cooperation with criminal investigation bodies is fundamental to identify not only cheating individuals but uncover whole networks. The use of certain substances and methods should be considered under criminal law. Structural preventive measures can contribute an important part, but must go hand in hand with values-based education. Spreading information must not be misjudged as education and education without research is like testing without intelligence: A waste of time, money, and effort. Some propositions of this paper could be implemented immediately,while others will take effect in the long run; nevertheless, each step is important to protect the clean athletes.